PENGARUH EDUKASI DENGAN MEDIA E-BOOKLET TENTANG ASI EKSKLUSIF DAN MAKANAN PENDAMPING ASI (MP-ASI) TERHADAP PENGETAHUAN DAN SIKAP IBU HAMIL DALAM PROGRAM PENCEGAHAN STUNTING - Apriliyanti, Devi; Noviardhi, Astidio; Subandriani, Dyah Nur (JURNAL RISET GIZI, 2022)
Background : Stunting is a nutritional problem that is still the focus of the government. Factors causing stunting in toddlers are knowledge, attitudes and skills of pregnant women regarding exclusive breastfeeding and complementary feeding and food intake including breast milk and complementary feeding. The prevalence of stunting in the Dukuhturi Health Center working area increased from 0,17% to 9,95% making it one of the top 4 highest stunting prevalence in Tegal Regency.Objective : Knowing the effect of education with e-booklet media about exclusive breastfeeding and complementary feeding on the knowledge and attitudes of pregnant women.Method : This type of research is quasi experimental with a pre test-post test design with a control group design. The research subjects were 17 pregnant women in each group which were selected by purposive sampling. The data collected includes data on knowledge and attitudes during pre test and post test. Data analysis was tested with Paired Samples T Test and Man Whitney.Result : There was an increase in knowledge and attitudes before and after receiving education in the intervention group and control group with p value 0,05. There are differences in knowledge and attitudes scores between the intervention group and the control group, so it can be concluded that the education delivered by e-booklet has a significant effect (p value 0,05) on the knowledge and attitudes of pregnant women.Conclusion : There is an effect of education using e-booklet media on the knowledge and attitudes of pregnant women regarding exclusive breastfeeding and complementary feeding.